Species introduction and taxonomic homogenization of Spanish freshwater fish fauna in relation to basin size, species richness and dam construction. Issue 1 (1st January 2018) - Castaño-Sánchez, Andrea; Valencia, Laura; Serrano, José M.; Delgado, Juan A.
Abstract: The introduction of exotic species is a key global threat to biodiversity. Beyond an increased risk of native species extinction, there exists a loss of biodiversity distinctiveness. Nevertheless, quantitative information on biotic homogenization at the taxonomic level in relation to basin features is rare. We used freshwater fish distribution data in Spain at three different time periods (1952, 1995, and 2007) to assess the species introduction process and the temporal dynamics of taxonomic homogenization among river basins in relation to basin size, native species richness and dam construction variables. The degree of alteration of original faunas by species introduction has increased through time, especially in native richer species, which suggest that the number of non-native and native species covariate with environmental heterogeneity. On the other hand, neither basin size nor habitat modification by dam construction seems to explain the number of introduced species. Our results indicate that the taxonomic homogenization of Spanish fish fauna is a temporally and spatially dynamic process; initial local increases in β-diversity through species introduction could be blurred because of scaling to regional and national levels or by the continuous expansion of a reduced number of exotic species.